(untitled) - Thompson, Wayne C. (Harpers Ferry, W. Va., 1998)
Contents: West Europe Today; The German-speaking Democracies; The French Republic; The Benelux Countries;...
Keywords: Europe,Politics and government,Châu Âu; Chính trị và chính phủ